PENGARUH PROXY EODB TERHADAP PEMBENTUKAN BISNIS DAN KAPITALISASI PASAR: STUDI KASUS PADA NEGARA BERPENGHASILAN RENDAH DAN MENENGAH - Abdul Gani (Jurnal Ekonomi Manajemen dan Bisnis, 2022)
The purpose of this study is to determine and analyze the effect of the proxies that facilitate the efforts formulated on the EODB ranking on new business formation and market capitalization. This research is conducted in low and middle countries, with the reach of low and middle countries covering 212 countries and spanning from 2010 to 2020. The methodology used in this research is the Generalized Method of Moment (GMM). GMM is used in this study considering the characteristics of the data in the form of a short data panel (short panel). In addition, regarding the characteristics of the data, the assumption of parallel data as one of the prerequisites for simple linear regression analysis as well as differences cannot be ascertained. In addition, the GMM method can be used to overcome problems where there is a risk of correlation between groups of results over the observation period which can lead to an underestimated standard error estimate. The results of this study indicate, among others: 1) there is an effect of the ease of doing proxies formulated in the EODB assessment on the formation of new businesses. 2) there is an effect of the ease of doing business proxy formulated on the EODB assessment of market capitalization.